ALLY 2 - Hoyle, Brian (MD Conference Express, 2015)
Results of the ALLY 2 trial involving more than 200 patients co-infected with HIV/HCV shows the efficacy and safety of the combined 12-week use of daclatasvir and sofosbuvir, with sustained virologic response for 12 weeks of 97% after a 12-week treatment. The benefit for HCV infection does not compromise the ongoing antiretroviral therapy.